Nicolau Syndrome: An Unforeseen Yet Evadable Consequence of Intramuscular Injection - Sasmal, Prakash K.; Sahoo, Ankit; Singh, Pradeep Kumar; VS, Vikram (The Surgery Journal, 2021)
An intramuscular (IM) injection is one of the common routes for administering drugs, commonly analgesics and vaccines. Nicolau syndrome refers to the rapid-onset painful, extensive cutaneous discoloration progressing to necrosis and ulceration, reported after IM injections. This case report highlights a rare but avoidable complication of such injections. An elderly man presented with extensive cutaneous necrosis and discoloration over the buttocks extending to the thigh, within few days after receiving a single shot of IM injection of diclofenac. Management involved wound care, biopsy, and cultures with supportive antibiotics to control superadded infection. After multiple sittings of extensive surgical debridement, the wound showed signs of healing and was ultimately amicable for skin grafting in a month.Health care workers need sensitization toward such a complication that can occur out of a routine procedure like an IM injection. They should follow standard IM injections techniques and take precautions to avoid this mishap, which adds to the patient's morbidity.
Keywords: intramuscular diclofenac; embolia cutis medicamentosa; dermatitis; necrotizing fascitis